Género, turismo y exportación: ¿llamando a la plata en el Perú? - Henrici, Jane (2007)
This article offers a brief description of the cases of some women living in the region of Cusco, Peru, who are involved in the production or sale of ethnic objects for the tourist and the export markets. The analysis shows that, while social agents usually emphasize cultural equality and exchange in their discourse, in practice their participation in these circuits tends to reinforce economic and political inequalities.